2014
DOI: 10.1177/0148607114546533
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Enteral Feedings in Critically Ill Children Receiving Vasoactive Agents

Abstract: Enteral feeding in patients receiving VAs is associated with no difference in GI outcomes and a tendency towards lower mortality. Prospective studies are required to confirm the safety of enteral feedings in patients receiving VAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 35 publications
3
37
0
1
Order By: Relevance
“…Interestingly, severity of illness scores have not been shown to predict the safety and tolerance of EN and there is no recognized risk of mortality above which EN is contraindicated (26, 27). In addition, observational studies have described the safety and benefits of EN in children on vasopressors and threats posed by these agents may be related to the particular vasopressor/s or doses employed (28-30)…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, severity of illness scores have not been shown to predict the safety and tolerance of EN and there is no recognized risk of mortality above which EN is contraindicated (26, 27). In addition, observational studies have described the safety and benefits of EN in children on vasopressors and threats posed by these agents may be related to the particular vasopressor/s or doses employed (28-30)…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported that enteral feeding was tolerated in patients on nonescalating/weaning doses of vasoactive agents without increased adverse effects or gastrointestinal complications [368][369][370]. In another study of 339 critically ill children, there was no association between enteral feeding and the development of severe gastrointestinal outcomes such as vomiting, diarrhea, abdominal distension, bleeding, necrotizing enterocolitis, or perforation [368]. However, in the report, the decision to start enteral nutrition may have been biased by the clinical condition of the patient.…”
Section: Rationalementioning
confidence: 99%
“…2012 [5] Before and after study To test the impact of a feeding protocol Emesis, elevated GRV × 2, or elevated GRV × 1 and abdominal girth increase Panchal et al 2014 [28] Retrospective observational…”
Section: Gastric Residual Volumementioning
confidence: 99%